Details of the Makara Torana - Temples of India Project Team (Jio Institute, 2024)
Details of the makara torana (ornamental archway flanked by crocodile-like mythical creatures at both ends) and frontal pediment of the shikhara, of the mukhamandapa (front porch), Ghateshwar Temple.